2014
DOI: 10.1002/anie.201310416
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Diruthenium and Dirhodium Analogues of Pentaborane(9): Agostic versus Boratrane Complexes

Abstract: A series of novel Cp*-based (Cp*=η(5)-C5Me5) agostic, bis(σ-borate), and boratrane complexes have been synthesized from diruthenium and dirhodium analogues of pentaborane(9). The synthesis and structural characterization of the first neutral ruthenadiborane(6) analogue are also reported. This new route offers a very efficient method for the isolation of bis(σ-borate) and agostic complexes from diruthenapentaborane(9).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 46 publications
3
47
0
5
Order By: Relevance
“…With the objective to synthesize analogues of 1 , we carried out the reaction of [Re 2 (CO) 10 ] with Na[(H 3 B)bbza], which yielded the octahedral complex [Re(CO) 2 (N 3 C 2 S 2 C 12 H 8 ) 2 ] ( 2 ), most probably by elimination of a BH 3 unit from the Na[(H 3 B)bbza] ligand (Figure S1 in the Supporting Information). We have recently reported various σ‐borate and agostic complexes that contain 2‐mbz‐based borate ligands . This prompted us to assess the reactivity of Na[(H 3 B)abz] (abz=2‐aminobenzothiazolyl) in the presence of [Mn 2 (CO) 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the objective to synthesize analogues of 1 , we carried out the reaction of [Re 2 (CO) 10 ] with Na[(H 3 B)bbza], which yielded the octahedral complex [Re(CO) 2 (N 3 C 2 S 2 C 12 H 8 ) 2 ] ( 2 ), most probably by elimination of a BH 3 unit from the Na[(H 3 B)bbza] ligand (Figure S1 in the Supporting Information). We have recently reported various σ‐borate and agostic complexes that contain 2‐mbz‐based borate ligands . This prompted us to assess the reactivity of Na[(H 3 B)abz] (abz=2‐aminobenzothiazolyl) in the presence of [Mn 2 (CO) 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…As part of our ongoing studies on the synthesis of electron‐precise transition‐metal–boron complexes from metallaboranes, we have recently reported several σ‐borate/B‐agostic complexes from the reaction of [(Cp*Ru) 2 B 3 H 9 ] with the 2‐mercaptobenzothiazolyl (mbz) ligand (Cp*=η 5 ‐C 5 Me 5 ) . Alternatively, we have shown that these complexes can also be generated from the reaction of [Cp*MCl 2 ] 2 (M=Ru, Rh, or Ir) with Na[H 2 B(mbz) 2 ] .…”
Section: Introductionmentioning
confidence: 99%
“…The B⋅⋅⋅Ru bond distances of 2.697(4) in 4 and 2.736(4) Å in 5 are analogous to [Cp*Ru{κ 3 ‐H,S,S′‐H 2 B(bt) 2 }] (2.753(1) Å). However, the Ru⋅⋅⋅H−B bond distance of 1.692(2) Å and 1.755(3) Å for 4 and 5 are shorter as compared to [Cp*Ru{κ 3 ‐H,S,S′‐H 2 B(bt) 2 }] 1.830(3) Å …”
Section: Resultsmentioning
confidence: 99%
“…Our group has also been actively involved in the synthesis of electron‐precise transition‐metal–boron complexes, especially from metallaborane species . This has led to the isolation of several triply‐bridged trimetallic borylene, boryl, diborane, and B‐agostic complexes . In an effort to find efficient methods for the preparation of such complexes, we used different synthetic precursors.…”
Section: Introductionmentioning
confidence: 99%